Fides caritate formata. Los polos extremos del Barroco: protestantismo y catolicismo en el Trauerspielbuch de Walter Benjamin - Cruz Aponiuk, Juan (Pontificia Universidad Católica del Perú, 2025)
This paper provides a commentary on the Trauerspielbuch, Walter Benjamin’s rejected habilitation thesis. It aims to fill a significant gap in the reception of the text by highlighting a fact that has been systematically ignored: that the Baroque presented by Benjamin is characterized by two extreme poles in tension –a Protestant pole, which has been extensively commentated upon, and a Catholic pole, consistently silenced–. Likewise, this implies a reinterpretation of decisive Benjaminian themes: romanticism, capitalism as a religion, the allegorical, destiny, nakedness, melancholy, and sovereignty. If, in the posthumous fragment Kapitalismus als Religion, Benjamin diagnosed capitalism as a parasitic religion of Christianity, powerful enough to force Christianity to convert to capitalism through Protestantism, it will be in the Trauerspielbuch where he studies this conversion more closely. The signature of conversion is sola fide or naked faith, which plunges into greater desolation those who are more pious, as it leaves them without criteria to discern between the Kingdom and the Antikingdom, between salvation and damnation. Opposing it, through the baroque dialectical apotheosis, is the fides caritate formata that unites faith with works.

El siguiente artículo es un comentario al Trauerspielbuch, la tesis de habilitación jamás aprobada de Walter Benjamin. Por ello, busca subsanar una enorme laguna en la recepción del texto, pues ha sido sistemáticamente ignorado que el Barroco que nos presenta Benjamin está compuesto por dos polos extremos en tensión, uno protestante extensamente glosado y otro católico, una y otra vez silenciado. Asimismo, esto implica una relectura de temas benjaminianos decisivos: el romanticismo, el capitalismo como religión, lo alegórico, el destino, la desnudez, melancolía y soberanía. Si, en el fragmento póstumo Kapitalismus als Religion, Benjamin diagnosticó al capitalismo como una religión parasitaria del cristianismo, suficientemente poderosa como para forzarlo a convertirse al capital a través del protestantismo. Es en el Trauerspielbuch donde estudia tal conversión con mayor detenimiento. La signatura de dicha conversión es la sola fide o fe desnuda, la cual hunde en una mayor desolación a aquellos que la práctican con mayor piedad, puesto que los deja sin criterio alguno para discernir entre el Reino y el Antirreino, entre la salvación y la condenación. Opuesta a tal signatura, especialmente a través de la apoteosis dialéctica barroca, se encuentra la fides caritate formata que une a la fe con la obra.
Fides caritate formata. The Extreme Poles of the Baroque: Protestantism and Catholicism in Walter Benjamin’s Trauerspielbuch
Keywords: Baroque; Theology; Politics; Sovereignty; Capitalism; Barroco; Teología; Política; Coberanía; Capitalismo; https://purl.org/pe-repo/ocde/ford#6.03.01